2016
DOI: 10.1902/jop.2016.150684
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Agents Used in the Treatment of Peri‐Implantitis Alter the Physicochemistry and Cytocompatibility of Titanium Surfaces

Abstract: ChA-specific residues left on the titanium surfaces altered titanium physical properties and adversely affected the osteoblastic response irrespective of their observed antimicrobial effect. Chlorhexidine may compromise the biocompatibility of titanium surfaces, and its use is not recommended to detoxify implants. Sterile saline, citric acid, and NaOCl-EDTA may be proposed for use in the treatment of peri-implantitis. Contrary to previous studies that recommended the selection of ChAs for the decontamination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
110
2
23

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(153 citation statements)
references
References 39 publications
15
110
2
23
Order By: Relevance
“…A previous study revealed that EDTA could be used to manage infected wounds [15]. Also, EDTA is used in the clinical setting to treat patients with otitis [16,36], for the treatment of peri-implant infections [17], and for the management of catheter-related infections [18,37]. To explore whether the effect of EDTA observed in vitro could be clinically significant in the lungs, a guinea pig model was established with PA infection in the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study revealed that EDTA could be used to manage infected wounds [15]. Also, EDTA is used in the clinical setting to treat patients with otitis [16,36], for the treatment of peri-implant infections [17], and for the management of catheter-related infections [18,37]. To explore whether the effect of EDTA observed in vitro could be clinically significant in the lungs, a guinea pig model was established with PA infection in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its chelating action, EDTA might exert its effects on biofilms and bacteria through other mechanisms, such as inhibition of efflux pump [13] and downregulation of mexA and mexB in PA [14]. Previous studies have shown that EDTA can be used to treat superficial infected wounds, as well as otitis, peri-implant infections, and catheter-related infections [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported that citric acid causes a reduction in biofilm in vitro but still leaves a biocompatible surface. 165,167,171 This is consistent with the present observations of 40% citric acid applied for 60 seconds giving good biofilm removal and no surface alterations.…”
Section: Discussionsupporting
confidence: 92%
“…170 There are important limitations in past work regarding citric acid, including the ability of citric acid-treated Ti surfaces to support cellular attachment. 171 Little is known regarding citric acid effects on various types of implant surfaces. For example, Wheelis et al reported the effects of various solutions on Ti surface roughness, but the starting point was a smooth rather than textured surface.…”
Section: Citric Acidmentioning
confidence: 99%
See 1 more Smart Citation